Efek Lama Proses Amofer terhadap Protein Kasar dan Lignin Kulit Buah Kakao - Firgian Ardigurnita; Nurul Frasiska; Novia Rahayu (LPPM Perjuangan University of Tasikmalaya, 2022)
Indonesia is the third largest cocoa producer and exporter in the world after Ghana and Ivory Coast. Cocoa production in Indonesia in 2020 is 720,660 tons. Cocoa pods have good nutritional potential for ruminants which include 17.2% dry matter; organic matter 81.2%; crude protein 9.07%; neutral detergent fiber (NDF) 73.9%; acid detergent fiber (ADF) 58.98%; cellulose 38.65%; and lignin 20.15%. The purpose of this study was to determine the optimal time for making feed from cocoa pods using ammonia and fermentation (amofer) processes. This study used a completely randomized design (CRD) consisting of 5 treatments for the ammonia fermentation process (Amofer) with 5 replications. The research treatments were: P0 = cocoa pods without urea and without Aspergillus Niger, P1 = cocoa pods + urea 6% + Aspergillus Niger 0.31% + Mineral mix 2% for 7 days, P2 = Cocoa pods + urea 6% + Aspergillus Niger 0.31% + Mineral mix 2% for 14 days, P3 = cocoa pod + urea 6% + Aspergillus Niger 0.31% + Mineral mix 2% for 21 days P4 = cocoa pod + urea 6% + Aspergillus Niger 0.31% + Mineral mix 2% for 28 days. The results showed that the moisture content of the ammonium pod peel on day 0 was significantly different (P<0.05) with the moisture content on the 7th, 14th, 21st and 28th days. The variables measured were nutritional content which included water content, ash content, crude protein (PK) and total lignin. The data obtained were analyzed using analysis of variance and continued with the orthogonal polynomial test. The ash content on the 14th, 21st and 28th days of making cocoa pods using the ammonia fermentation (amofer) method using urea and Aspergillus Niger (P<0.05) was significantly different from the control. The results of crude protein analysis on the 7th, 14th, 21st and 28th days of making cocoa pods using the ammonia fermentation (amofer) method using urea and Aspergillus Niger (P<0.05) were significantly different from the control. The results of the analysis of total lignin on the 7th, 14th, 21st and 28th days of making cocoa pods using the ammonia fermentation (amofer) method using urea and Aspergillus Niger (P<0.05) were significantly different from the control. The conclusion of the treatment of cocoa pod peel with amofer is that the addition of urea 6% + Aspergillus Niger 0.31% + Mineral mix 2% with a difference in treatment time of up to 28 days can increase crude protein and water content and reduce ash content and total lignin. Keywords: amofer, ammoniation, fermentation, cocoa pods, feed. Keywords: amofer, ammonia, fermentation, cocoa fruit peel, feed.